PROBLEM OF METABOLIC DISORDERS IN CHILDREN WITH JUVENILE ARTHRITIS LIVING IN THE REPUBLIC OF MORDOVIA - A. V. Krasnopolskaya; L. A. Balykova; T. I. Kornilova; A. A. Shirokova (Научно-практическая ревматология, 2014)
It is assumed that juvenile idiopathic arthritis (JIA), as many other rheumatic diseases, is in close pathogenic connection with metabolic disorders and early atherosclerosis. However, the prevalence of metabolic syndrome and its components both in healthy Finno-Ugrian children and teens and JIA patients is unknown.Objective of the present work was to study the prevalence of metabolic disorders in children with JIA, living in the Republic of Mordovia.Subjects and methods. Authors have examined 82 children (among them 44 girls) with JIA aged 10–18 years. Results. Full complex of metabolic syndrome symptoms was revealed in 36.6% of patients, most of which had arthritis. Dyslipidaemia, obesity and arterial hypertension were recorded most frequently and correlated with activity of the disease and the dose of systemic glucocorticoids.Conclusion. JIA is associated with high prevalence of metabolic disorders which only partially (arterial hypertension and carbohydrate metabolism disorders) are connected with glucocorticoid therapy and mainly determined by the high inflammatory activity of the disease.